(untitled) (Fiep Bulletin - online, 2013)
I have always believed in many things as the ability of human growth, which we did not come to the world by chance, that to love anything is possible, that we all have a mission in life, not just think about it as I’m sure that God in preparing to hold our mission in the best possible way. I was blessed to have a daughter with Down syndrome (DS), which is the greatest gift that I received. For this love, I am here showing that intensive physiotherapy daily in the three first years of life of children with Down syndrome, makes its development more effectively. I hope that from the experience with Barbara Francielle (BF) and the method used for their wonderful development, may prove that children can and Down has the right to have a life full of achievements and happiness, thus minimizing the differences. The arrival of a baby for most families is very special, is a moment of realization of dreams, happiness, plans for the future, after all, want this child is the most "perfect", the most beautiful, most intelligent. And on the big day, the doubts, - "Is that going nascer with some defect?". The science shows that Down syndrome has limitations in intellectual level and the development engine, but the greatest sadness is to see that the pre-concept comes from society and has no limitations. Handling was when my daughter did not know was that the benefits it provides, in the beginning was not aware, only a few professional tips, intuition, love and very sure that there are barriers to be overcome. He said wisely Werneck (1995) "Every child, with or without mental retardation, needs to learn to stimuli by dragging, crawling, sitting, walking, talking. Just as adults, although intuitively work accordingly, do not give account of what they do. Each new game, every trip to the circus or the parquinho of entertainment, every song you sing, every trip, every activity at the time of the bath or during a meal, we are encouraging them. "During my pregnancy, and early in life for Barbara, I heard much criticism, prejudice, people saying that my daughter would not be able, I did not expect much of it. This all could have done a fragile person desist from any attempt of any hope, but God gave me strength and confidence to challenge everyone, if they were needed. Because nothing and no one would make me stop believing that we have the ability to modify and improve their lives.